Management practices and public policy: an overview. (29th June 2021) - Quinn, Simon; Scur, Daniela
Abstract: This paper introduces and summarizes this issue of the Oxford Review of Economic Policy, on management practices. We outline key concepts in the empirical study of structured management practices, then summarize each of the eight papers that follows. We conclude by speculating on future directions for research and policy development in this area.